O monstruoso no imaginário social limenho em fins do século XVII - Silva, Kawany Stephany da (2021)
By addressing the historical context of the capital of Peru's viceroyalty, Lima, during the second half of the 17th century, this dissertation seeks to understand how the process of instituting itself in the field of imaginary and social values and standards works in a society that lead to the formation of ways of living and organizing collectively. Therefore, it will be analyzed one case about a bicipital birth, considered as monstrous, studied in a teratological treatise published in Lima in the year of 1695. To think the notion of the order and detour is fundamental to comprehend how the deformed body becomes a social deviation and how theses imaginaries are instituted and established in society. In a concomitantly way, we also analyzed the historical process of inclusion of the deformed body and monstrous in medical science, as an object of study that seeks for scientific explanations and possibilities of cure or medication. The science of the late seventeenth and early eighteenth century approached the deformed and the infirm under the same epistemological basis as natural history, where the deviant is no longer excluded while social individual and begins to be integrated and adjusted from the standards and principles of that society. At the end of the analysis, we concluded that monstrous bodies can thus be defined based on political relations and that those considered deviant are also considered political persons. The functionality or dysfunctionality of a body, as well as a society, is discussed and legitimized through political conflicts that define the levels of normality depending on its social context and which social group accesses the political power.